Preventable public health challenge: Rabies suspected exposure and prophylaxis practices in southwestern of Turkey - Nefise Oztoprak; Hande Berk; Filiz Kizilates (Elsevier, 2021)
Background: Rabies is found in many countries of the eastern Mediterranean and is one of the most important zoonotic diseases in the world. The study aims to describe rabies suspected exposures (RSE) and rabies prophylaxis practices in Antalya-Turkey between 2010 and 2013. Methods: All 2513 RSE cases presenting to a rabies vaccination center in Antalya, southwestern Turkey, were retrospectively investigated. Results: The mean age of the RSE cases was 30.04 ± 19.63 years with male predominance (63.6%). The vast majority was from urban areas (91.7%), and a postexposure rabies vaccination program was applied to 79.7% of participants. Dogs were the primary source of RSE cases (61.2%). The 39.2% of animals were under observation, and 9.53% of them died. Forty-two animals (1.7%) were laboratory confirmed rabid; 61.9% of them were cows. The rabid animal rate in the rural area was significantly higher than the urban area (18.2% versus 0.2%; p = 0.001). Conclusions: This study includes a large number of RSE cases and prophylaxis practices in southwestern Turkey. Most RSE cases had dog or cat contact. As most RSE cases were in urban areas; more focused efforts should be made for elimination and vaccination of feral dog and cat population in Turkey.